Exploring Nonmotor Neuropsychiatric Manifestations of Parkinson Disease in a Comprehensive Care Setting. (May 2021) - Dhingra, Amitha; Janjua, A. Umair; Hack, Laura; Waserstein, Gabriella; Palanci, Justin; Hermida, Adriana P.
Parkinson disease (PD) is a debilitating neurological condition that includes both motor symptoms and nonmotor symptoms (NMS). Psychiatric complaints comprise NMS and are collectively referred to as neuropsychiatric manifestations. Common findings include atypical depressive symptoms, anxiety, psychosis, impulse control disorder, deterioration of cognition, and sleep disturbances. Quality of life (QoL) of patients suffering from NMS is greatly impacted and many times can be more debilitating than motor symptoms of PD. We expand on knowledge gained from treatment models within a comprehensive care model that incorporates multidisciplinary specialists working alongside psychiatrists to treat PD. Insight into background, clinical presentations, and treatment options for patients suffering from neuropsychiatric manifestations of PD are discussed. Identifying symptoms early can help improve QoL, provide early symptom relief, and can assist tailoring treatment plans that limit neuropsychiatric manifestations.